Town-planning Organization of the Baku Industrial Region: 19th – 20th Centuries - Abdullayeva, Nargiz; Bakirova, Tarana; Ayten Rahmanova (Politechnika Lubelska, 2020)
The article considers the emergence in the modern town-planning practice of Azerbaijan complex planning sys-tems require comprehends to historical experience, especially the end of the nineteenth beginning of thetwentiethcenturies.The industrial revolution started in the middle of the 19th century in connection with the development of the oil industry accelerated the process of urbanization in Absheron also in Baku the centre of population concentration and various types of labour activity. The purpose of the study is to present Baku oil district at the turn of the 19th-20thcenturies to reveal communications and interactions between social, demographic and other processes as a complex organism with all contradictions inherent in the epoch of rapid development of capitalism which has received the material expression in the form of the newly developed planning system.